Effect of Vasectomy and / or Adding Cuminum cyminum Seeds in the diet of Awassi Ram Lambs on their Carcasses Traits: Tamara N. Dawood@ and Mudhaffar N.R. AL-Saigh - Dawood, Tamara N. (The Iraqi Journal of Veterinary Medicine, 2014)
This experiment was carried out at Animal Farm, College of Veterinary Medicine, Baghdad University, from Mar. up to Sept. 2010. Twenty eight Awassi ram lambs of 4-5 months old were equally divided into four groups of similar body weight and fed 2% of concentrate diet of body weight with grazing for 3-4 hours a day. The first group (C) and the third group (V) were fed concentrate diet free of cumin seeds; while the second group (CU) and the fourth group (CV) were fed the same amount of concentrate diet contain 3% of cumin seeds. All animals were grazed daily for 3-4 hours as one group. The third and the fourth groups were vasectomized by close vasectomy operation at the beginning of the experiment. The results revealed that cumin seeds used as feed additives for Awassi ram lambs caused significant (P<0.05) increase in live animal body weight, fasting and empty body weight, hot and cold carcass weights also it had an effect on carcass measurements, empty digestive and stomach weight, most carcass joints weight, rib eye muscle area, Longismus dorsi weight, lean and fat weight in the rack joint compare with the control group. However vasectomy had significant (P<0.05) increase in the body weight, fasting, empty and hot and cold carcass weight, the weight of pelt, full and empty digestive system, most of joint weights, fat tail, fat weight of the rack joint, while the 4th group showed higher values than the most carcass traits compared with the 2nd and 3rd groups and significantly (P<0.05) higher than the control group (1st group). It is concluded that vasectomy and cumin seeds have positive effect on lamb performance and carcass traits. Cumin seeds can be used as effective and cheep feed additives. Further studied are required to prove the suitable ratio of cumin seeds addition alongside with castration in other farm animals.